Rapid Assessment for Coexistence of Vitamin B12 and Iron Deficiency Anemia among Adolescent Males and Females in Northern Himalayan State of India - Ashok Bhardwaj; Dinesh Kumar; Sunil Kumar Raina; Pardeep Bansal; Satya Bhushan; Vishav Chander (Anemia)
Coexistence of folic acid and vitamin B12 deficiency has been observed among adolescents with iron deficiency anemia, but limited evidence is available from India. So, a rapid assessment was done to study the prevalence of iron, folic acid, and vitamin B12 deficiency among adolescent males and females in northern Himalayan state in India. Methods. Total 885 (female: 60.9%) adolescents (11 to 19 completed years) were surveyed from 30-cluster village from two community development blocks of Himachal Pradesh. Serum ferritin, folic acid, and vitamin B12 were estimated among randomly selected 100 male and 100 female adolescents. Results. Under-nutrition (BMI < 18.5 kg/m2) was observed among 68.9% of adolescents (male: 67.1%; female: 70.7; ). Anemia was observed to be prevalent among 87.2% males and 96.7% females (). Mild form of anemia was observed to be the most common (53.9%) form followed by moderate (29.7%) anemia. Strikingly, it was found that all the adolescents were deficient in vitamin B12 and none of the adolescents was observed to be deficient in folic acid. Conclusion. Among both male and female adolescents anemia with vitamin B12 deficiency was observed to be a significant public health problem. Folic acid deficiency was not observed as a problem among surveyed adolescents.